The Effect of Heuristics (Anchoring Availability) and Risk Tolerance on Portopolio Diversifacation with Finansial Planning as a Mediator Gen Z in Surabaya City - Nurul Iman; Elly Yuniar Nitawati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study examines the behavioral determinants of portfolio diversification among Generation Z investors in Surabaya City, focusing on the role of cognitive biases and financial behavior in shaping investment decisions. In the context of increasing participation of young investors in financial markets, understanding how heuristics and risk preferences influence diversification has become increasingly important. The objective of this research is to analyze the effects of anchoring heuristic, availability heuristic, and risk tolerance on portfolio diversification, with financial planning as a mediating variable. This study employs a quantitative explanatory approach using a cross-sectional survey design. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The results indicate that all variables have a significant effect on portfolio diversification, with risk tolerance emerging as the strongest predictor. Financial planning is also found to play a significant mediating role, strengthening the influence of cognitive and behavioral factors on diversification decisions. These findings confirm that investment behavior among Generation Z is influenced not only by rational considerations but also by cognitive biases and structured financial management practices. This study contributes to behavioral finance literature by integrating psychological and behavioral factors into a unified model and provides practical implications for improving financial decision-making through enhanced financial planning and risk awareness.